INVENTARISASI DAN PENGKAJIAN TANAMAN EMPON - EMPON DI DESA PARE KECAMATAN KRANGGAN KABUPATEN TEMANGGUNG - Siti Nurul Iftitah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The demand for rhizomes (empon-empon) is increasing along with public awareness of health and the use of herbal ingredients. Indonesia boasts numerous varieties of rhizomes, each with unique properties that can be used in traditional herbal medicines. These plants can be planted as monocultures in open fields or intercropped under perennial crops (agroforestry). This research aims to identify the types of rhizomes available, to understand the appropriate cultivation methods for these plants, and to motivate farmers to cultivate rhizomes in accordance with Good Agricultural Practices (GAP).This resulted in the production of high-quality herbal plants that could be accepted in the herbal medicine industry. The research was conducted using a descriptive method, namely by inventorying, identifying, and assessing several types of existing herbal plants. Observations were conducted on 15 farmer samples divided into three hamlets. The results showed that the majority of Pare Village residents still knew and owned herbal plants, such as ginger, turmeric, and galangal, grown in dry fields without observing proper cultivation methods or GAP (Growth Approach). There was no processing of these herbal plants, so training on processing them was needed to increase the income of farming families.